3PC-012 Impact of preliminary wiping of equipment introduced into a cleanroom on the control of the environment. (23rd March 2022) - Durieux, F; Nassar, C; Lannoy, D; Odou, P
Abstract : Background and importance: Parenteral nutrition is a high-risk activity. It is necessary to master and control the preparation environment. Within our parenteral nutrition unit, a decontamination airlock (Malochet) with hydrogen peroxide (H2 O2 ) (Clarus, Bioquell) is used to bring the equipment (medical devices, glass nutrient bottles) into the cleanroom. They are introduced directly from an ISO 8 area into the airlock, without systematic wiping. Aim and objectives: The goal was to improve environmental control by studying the impact of preliminary wiping of equipment entering the cleanroom before or after surface decontamination with H2 O2 . Material and methods: The same operator performed surface swabs on medical devices (paper and plastic sides) and glass nutrient bottles. The wiping method was the same for all: 1 pre-impregnated wipe (55% ethanol and quaternary ammonium propionate) per piece of equipment. The airlock was qualified (4 log decontamination, 9-min dwell phase). 6 cycles were performed for 70 samples. For each cycle, before decontamination, 3 swabs were carried out after a prior wiping (on plastic, glass and paper sides) and 4 without wiping (on plastic, glass and two paper sides), then 7 swabs on those pieces of equipment after decontamination. Inoculation on trypto-casein soy agar was performed for each swab. Agar plates were incubated for 3 days at 32°C and 4 days at room temperature. Colony-forming units (CFU) were read on days 3 and 7. Data were collected in an Excel file and analysed with Mann–Whitney and Welch tests. Results: The difference in the number of CFU at 7 days between the groups without wiping and with wiping before decontamination was significant (p<0.01) but not significant after decontamination (p=0.17). The difference between the groups before decontamination with wiping and after decontamination without wiping was not significant (p=0.079 ), but with a strong trend. Most of the contamination found after decontamination was bacteria. A mould was found after decontamination. Conclusion and relevance: This study shows that contamination brought in by equipment is possible. Wiping reduces the risk of contamination when decontamination by H2 O2 is not possible. It seems important to limit storage inside the cleanroom to avoid a release of contamination into the air. References and/or acknowledgements: Conflict of interest: No conflict of interest